O Benfica dos grafites nos anos 2000 - Pereira, Aleksandra Previtalli Furquim (2012)
This study analyzes graffiti as an artistic form of occupying the city, being able to produce some important educational initiatives. Graffiti is a kind of painting in the walls of a city used to portray the urban dilemmas of the beginning of this century. It has, inside it, history, characters, rules, clothing, vocabulary, conflicts, adventures, and actions that allows real conditions of inclusion, because it offers learning, participation, visibility, fame, goals, and opportunities that people who live inside this world can take, or not. It is in the streets that graffiti artists learn how to use the sprays, its techniques, its draws, and the strategies of appropriation of these spaces. In this context, this work’s text has as its objective focus on the educational practices of graffiti artists that do their job in Benfica neighborhood’s walls, in Fortaleza, Ceará, since the years of 2000s. Benfica is a neighborhood that nowadays is a reference not only for students and intellectual people, but also for many artists all over the state, because it reunites art, culture, and bohemia. We have here a multifarious movement in a way that we need to remember the thoughts of some authors as Gitahy, to describe the history of graffiti; Calvino, in the discussion about the cities; Baudrillard, in the simulacrum of signs; Coli and Lacoste, in the perceptions about the art and Pallamin about the public art; Brandão and Libâneo, about the education in the educational practices; Certeau, in the graffiti artists’ strategies. With the thoughts of these researchers, we are able to launch our eyes in this instigating topic in the educational point of view. What are the spaces occupied by the graffiti? Where and how the Benfica’s artistic painting has appeared? Who are the graffiti artists? Where we can track and find them? How do they learn to graffiti? How do they act? How do they organize themselves? How do their educational practices are stated? Is it possible to educate through the art? There are many questions about this social group answered in this work. We collected some graffiti artists’ quotes in interviews, in social networks in the internet, and in the journals that constantly deal with this issue. To sum up, we believe that with this work, we are contributing to the future researches about education and urban themes that appear in our society.